A MULTIMODAL DISCOURSE ANALYSIS ON SELENA GOMEZ’S REVIVAL ALBUM COVER AND MAIN HIT: A NOT-SO-REVIVAL - Sinaga, Mentari Putri Pramanenda (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
The magnificence and glamorous life of public figures including singers are not always ending happily. The works pressure and fans become parts of life conflicts. Haters couldn’t be also ignored since they spread negative words and rumours. However, as a professional, a singer keep being productive through her songs. The lyrics in the songs carry message that could be related to their privacy. Besides, their photograph in the album cover emblematizes a purpose. Through the multimodal discourse analysis, readers are well-told about the meaning behind the photograph and lyrics. The verbal aspects in the clauses have an ideology. Additionally, the non-verbal aspects of the album cover provide visual image, posture, gesture, facial expression and color. Thus, the study aims to analyze the ‘not-so-revival’ in lyrics and front cover image by Selena Gomez’s ‘Revival’ album.